2013
DOI: 10.1111/cei.12200
|View full text |Cite
|
Sign up to set email alerts
|

Trans fatty acids exacerbate dextran sodium sulphate-induced colitis by promoting the up-regulation of macrophage-derived proinflammatory cytokines involved in T helper 17 cell polarization

Abstract: SummaryNumerous reports have shown that a diet containing large amounts of trans fatty acids (TFAs) is a major risk factor for metabolic disorders. Although recent studies have shown that TFAs promote intestinal inflammation, the underlying mechanisms are unknown. In this study, we examined the effects of dietary fat containing TFAs on dextran sodium sulphate (DSS)-induced colitis. C57 BL/6 mice were fed a diet containing 1·3% TFAs (mainly C16:1, C18:1, C18:2, C20:1, C20:2 and C22:1), and then colitis was indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 51 publications
(69 reference statements)
0
27
0
Order By: Relevance
“…As in this experimental group we also observed an increase in RS generation accompanied by an increase in PC levels following AMPH treatment, we hypothesized that: (i) TFA present in neural membranes, even in small amounts, is a precursor of proinflammatory mediators such as cytokines and interleukines (Okada et al, ), favoring RS generation; (ii) AMPH increases dopamine (DA) output from neurons, whose autooxidation also favors RS generation; (iii) Oxidative processes can affect proteins from membranes, as observed by increased PC levels; (iv) Such protein damage seems to have impaired dopamine reuptake, as observed by reduced DAT levels . The reduced reuptake of DA increments DA levels in the synaptic cleft, whose autoxidation generates more pro‐oxidative metabolites; (v) TFA present in membranes may be interfering with DA signaling as well, exacerbating reactive species generation, whose levels were not adequately controlled by the antioxidant defense system; (vi) TFA in neural membranes may affect the synaptic plasticity (Larqué et al, ), modifying neurotransmission; and (v) Taken together, these processes may all be damaging the DNA, as observed by reduced levels of BDNF mRNA, impairing memory performance.…”
Section: Discussionmentioning
confidence: 72%
“…As in this experimental group we also observed an increase in RS generation accompanied by an increase in PC levels following AMPH treatment, we hypothesized that: (i) TFA present in neural membranes, even in small amounts, is a precursor of proinflammatory mediators such as cytokines and interleukines (Okada et al, ), favoring RS generation; (ii) AMPH increases dopamine (DA) output from neurons, whose autooxidation also favors RS generation; (iii) Oxidative processes can affect proteins from membranes, as observed by increased PC levels; (iv) Such protein damage seems to have impaired dopamine reuptake, as observed by reduced DAT levels . The reduced reuptake of DA increments DA levels in the synaptic cleft, whose autoxidation generates more pro‐oxidative metabolites; (v) TFA present in membranes may be interfering with DA signaling as well, exacerbating reactive species generation, whose levels were not adequately controlled by the antioxidant defense system; (vi) TFA in neural membranes may affect the synaptic plasticity (Larqué et al, ), modifying neurotransmission; and (v) Taken together, these processes may all be damaging the DNA, as observed by reduced levels of BDNF mRNA, impairing memory performance.…”
Section: Discussionmentioning
confidence: 72%
“…[113] In contrast, trans-fats appear to exacerbate DSS colitis through up-regulation of Th17 signaling. [114] Unfortunately, the results in human CD patients have been more mixed, with conflicting studies finding that omega-3 fatty acids either decreased the rate of relapse,[115] or had no effect on the remission rate[116]. …”
Section: Fatmentioning
confidence: 99%
“…Studies have shown that incorporation of TFA into cell membrane lipids changes the fluidity and associated receptor functions [4]. TFA enriched macrophages secrete high levels of pro-inflammatory interleukins and fibrinogen [5]. The TFA also affect the functions of peroxisome proliferator activated receptor (PPAR)γ [6].…”
Section: Introductionmentioning
confidence: 99%